Simulation of Black hole Nodes and Prevention Using IDS for MANET Reactive Routing Protocol AODV - Thakur, Bhagyashree; Patel, Sharda; Verma, Ashok; Dubey, Shivendu (International Journal of Computer Sciences and Engineering, 2014)
Mobile ad hoc networks (MANET) are widely used in that places where there is no available infrastructure. It is also called infrastructure less network. It is a collection of mobile nodes that dynamically form a temporary network without infrastructure. Each mobile node can move freely in any direction and changes their links to other devices frequently. In MANET different types of routing protocols have been recommended. Ad hoc On demand Distance Vector (AODV) is one of the most suitable routing protocol for the MANETs and it is more vulnerable to black hole attack by the malicious nodes. In this attack, the malicious node advertises itself as having the shortest path to the destination and falsely replies to the route requests, and drops all receiving packets. In this paper, we have surveyed and compare the existing solutions to multiple black hole attacks on AODV protocol and their drawbacks.